Immune response to potential diabetes-related dietary antigens, including Glb1 in patients with type 1 diabetes - Mojibian, Majid (University of Ottawa (Canada), 2007)
Type 1 diabetes (T1D) is a T cell mediated autoimmune disease dependent on gene-environment interaction. Food components are considered as environmental agents that influence the incidence of islet cell autoimmunity and T1D. Wheat proteins are harmless in healthy individuals, but in genetically susceptible individuals, wheat may be immunopathogenic. There are several reports that link wheat with increased risk of autoimmune diabetes. The major aim of this study was to determine whether there is an abnormal immune response to a mixture of wheat proteins (WP) or a purified wheat storage globulin homologue, Glb1 in T1D patients. If so, the question arises regarding the nature of the immune response and whether such reactivity is genetically controlled. A sensitive CFSE-based proliferation assay and a capture ELISA technique were established to evaluate T cell immune response and Glb1 antibody level. Studies of young adults with T1D indicated that a subset of patients displayed abnormal humoral and cellular immune response to Glb1. T cell responses to WP and Glb1 were predominantly Th1 type and were associated with the diabetes risk gene HLA-DR4, and not HLA-DQ2, the main coeliac disease (CD) risk gene, suggesting the effect was diabetes-specific. Additional studies in children at high risk for diabetes with islet autoimmunity revealed that Glb1 antibody and zonulin were highly correlated, suggesting the presence of gut abnormalities related to tight junctions. In addition, increased immune response to Glb1 was present in children at high risk for diabetes who developed antibodies to the CD autoantigen, tTG. Interestingly, Glbl antibodies appeared before tTG antibodies, suggesting that Glb1 antibody could have predictive value in people at risk of disease. The data from this study clearly demonstrate for the first time the presence of abnormal humoral and cellular responses to wheat related dietary antigens in patients with T1D. Further, these data strongly suggest that the gut is not functioning normally and raises the possibility of a defect in the gut barrier, an immune imbalance and/or impaired oral tolerance.
Keywords: Health Sciences, Immunology.